Calculator search results

Formula
Solve the quadratic equation
Answer
circle-check-icon
expand-arrow-icon
expand-arrow-icon
Number of solution
Answer
circle-check-icon
Relationship between roots and coefficients
Answer
circle-check-icon
Graph
$y = x ^ { 2 } - 8 x + 3$
$y = 0$
$x$-intercept
$\left ( 4 - \sqrt{ 13 } , 0 \right )$, $\left ( \sqrt{ 13 } + 4 , 0 \right )$
$y$-intercept
$\left ( 0 , 3 \right )$
Minimum
$\left ( 4 , - 13 \right )$
Standard form
$y = \left ( x - 4 \right ) ^ { 2 } - 13$
$x ^{ 2 } -8x+3 = 0$
$\begin{array} {l} x = 4 + \sqrt{ 13 } \\ x = 4 - \sqrt{ 13 } \end{array}$
Solve quadratic equations using the square root
$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 8 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 3 } = \color{#FF6800}{ 0 }$
$ $ Convert the quadratic expression on the left side to a perfect square format $ $
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 4 } \right ) ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 3 } \color{#FF6800}{ - } \color{#FF6800}{ 4 } ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ 0 }$
$\left ( x - 4 \right ) ^ { 2 } \color{#FF6800}{ + } \color{#FF6800}{ 3 } \color{#FF6800}{ - } \color{#FF6800}{ 4 } ^ { \color{#FF6800}{ 2 } } = 0$
$ $ Move the constant to the right side and change the sign $ $
$\left ( x - 4 \right ) ^ { 2 } = \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ + } \color{#FF6800}{ 4 } ^ { \color{#FF6800}{ 2 } }$
$\left ( x - 4 \right ) ^ { 2 } = - 3 + \color{#FF6800}{ 4 } ^ { \color{#FF6800}{ 2 } }$
$ $ Calculate power $ $
$\left ( x - 4 \right ) ^ { 2 } = - 3 + \color{#FF6800}{ 16 }$
$\left ( x - 4 \right ) ^ { 2 } = \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ + } \color{#FF6800}{ 16 }$
$ $ Add $ - 3 $ and $ 16$
$\left ( x - 4 \right ) ^ { 2 } = \color{#FF6800}{ 13 }$
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 4 } \right ) ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ 13 }$
$ $ Solve quadratic equations using the square root $ $
$\color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 4 } = \pm \sqrt{ \color{#FF6800}{ 13 } }$
$\color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 4 } = \pm \sqrt{ \color{#FF6800}{ 13 } }$
$ $ Solve a solution to $ x$
$\color{#FF6800}{ x } = \pm \sqrt{ \color{#FF6800}{ 13 } } \color{#FF6800}{ + } \color{#FF6800}{ 4 }$
$\color{#FF6800}{ x } = \pm \sqrt{ \color{#FF6800}{ 13 } } \color{#FF6800}{ + } \color{#FF6800}{ 4 }$
$ $ Separate the answer $ $
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ 4 } \color{#FF6800}{ + } \sqrt{ \color{#FF6800}{ 13 } } \\ \color{#FF6800}{ x } = \color{#FF6800}{ 4 } \color{#FF6800}{ - } \sqrt{ \color{#FF6800}{ 13 } } \end{array}$
$\begin{array} {l} x = 4 + \sqrt{ 13 } \\ x = 4 - \sqrt{ 13 } \end{array}$
Calculate using the quadratic formula
$x = \dfrac { \color{#FF6800}{ - } \left ( \color{#FF6800}{ - } 8 \right ) \pm \sqrt{ \left ( - 8 \right ) ^ { 2 } - 4 \times 1 \times 3 } } { 2 \times 1 }$
$ $ Simplify Minus $ $
$x = \dfrac { 8 \pm \sqrt{ \left ( - 8 \right ) ^ { 2 } - 4 \times 1 \times 3 } } { 2 \times 1 }$
$x = \dfrac { 8 \pm \sqrt{ \left ( \color{#FF6800}{ - } \color{#FF6800}{ 8 } \right ) ^ { \color{#FF6800}{ 2 } } - 4 \times 1 \times 3 } } { 2 \times 1 }$
$ $ Remove negative signs because negative numbers raised to even powers are positive $ $
$x = \dfrac { 8 \pm \sqrt{ 8 ^ { 2 } - 4 \times 1 \times 3 } } { 2 \times 1 }$
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 8 \pm \sqrt{ 8 ^ { 2 } - 4 \times 1 \times 3 } } { 2 \times 1 } }$
$ $ Organize the expression $ $
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 8 \pm \sqrt{ 52 } } { 2 \times 1 } }$
$x = \dfrac { 8 \pm \sqrt{ \color{#FF6800}{ 52 } } } { 2 \times 1 }$
$ $ Organize the part that can be taken out of the radical sign inside the square root symbol $ $
$x = \dfrac { 8 \pm \color{#FF6800}{ 2 } \sqrt{ \color{#FF6800}{ 13 } } } { 2 \times 1 }$
$x = \dfrac { 8 \pm 2 \sqrt{ 13 } } { 2 \color{#FF6800}{ \times } \color{#FF6800}{ 1 } }$
$ $ Multiplying any number by 1 does not change the value $ $
$x = \dfrac { 8 \pm 2 \sqrt{ 13 } } { \color{#FF6800}{ 2 } }$
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 8 \pm 2 \sqrt{ 13 } } { 2 } }$
$ $ Separate the answer $ $
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 8 + 2 \sqrt{ 13 } } { 2 } } \\ \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 8 - 2 \sqrt{ 13 } } { 2 } } \end{array}$
$\begin{array} {l} x = \color{#FF6800}{ \dfrac { 8 + 2 \sqrt{ 13 } } { 2 } } \\ x = \dfrac { 8 - 2 \sqrt{ 13 } } { 2 } \end{array}$
$ $ Do the reduction of the fraction format $ $
$\begin{array} {l} x = \color{#FF6800}{ \dfrac { 4 + \sqrt{ 13 } } { 1 } } \\ x = \dfrac { 8 - 2 \sqrt{ 13 } } { 2 } \end{array}$
$\begin{array} {l} x = \dfrac { 4 + \sqrt{ 13 } } { \color{#FF6800}{ 1 } } \\ x = \dfrac { 8 - 2 \sqrt{ 13 } } { 2 } \end{array}$
$ $ If the denominator is 1, the denominator can be removed $ $
$\begin{array} {l} x = \color{#FF6800}{ 4 } \color{#FF6800}{ + } \sqrt{ \color{#FF6800}{ 13 } } \\ x = \dfrac { 8 - 2 \sqrt{ 13 } } { 2 } \end{array}$
$\begin{array} {l} x = 4 + \sqrt{ 13 } \\ x = \color{#FF6800}{ \dfrac { 8 - 2 \sqrt{ 13 } } { 2 } } \end{array}$
$ $ Do the reduction of the fraction format $ $
$\begin{array} {l} x = 4 + \sqrt{ 13 } \\ x = \color{#FF6800}{ \dfrac { 4 - \sqrt{ 13 } } { 1 } } \end{array}$
$\begin{array} {l} x = 4 + \sqrt{ 13 } \\ x = \dfrac { 4 - \sqrt{ 13 } } { \color{#FF6800}{ 1 } } \end{array}$
$ $ If the denominator is 1, the denominator can be removed $ $
$\begin{array} {l} x = 4 + \sqrt{ 13 } \\ x = \color{#FF6800}{ 4 } \color{#FF6800}{ - } \sqrt{ \color{#FF6800}{ 13 } } \end{array}$
$ $ 2 real roots $ $
Find the number of solutions
$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 8 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 3 } = \color{#FF6800}{ 0 }$
$ $ Determine the number of roots using discriminant, $ D=b^{2}-4ac $ from quadratic equation, $ ax^{2}+bx+c=0$
$\color{#FF6800}{ D } = \left ( \color{#FF6800}{ - } \color{#FF6800}{ 8 } \right ) ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ \times } \color{#FF6800}{ 1 } \color{#FF6800}{ \times } \color{#FF6800}{ 3 }$
$D = \left ( \color{#FF6800}{ - } \color{#FF6800}{ 8 } \right ) ^ { \color{#FF6800}{ 2 } } - 4 \times 1 \times 3$
$ $ Remove negative signs because negative numbers raised to even powers are positive $ $
$D = 8 ^ { 2 } - 4 \times 1 \times 3$
$D = \color{#FF6800}{ 8 } ^ { \color{#FF6800}{ 2 } } - 4 \times 1 \times 3$
$ $ Calculate power $ $
$D = \color{#FF6800}{ 64 } - 4 \times 1 \times 3$
$D = 64 - 4 \color{#FF6800}{ \times } \color{#FF6800}{ 1 } \times 3$
$ $ Multiplying any number by 1 does not change the value $ $
$D = 64 - 4 \times 3$
$D = 64 \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ \times } \color{#FF6800}{ 3 }$
$ $ Multiply $ - 4 $ and $ 3$
$D = 64 \color{#FF6800}{ - } \color{#FF6800}{ 12 }$
$D = \color{#FF6800}{ 64 } \color{#FF6800}{ - } \color{#FF6800}{ 12 }$
$ $ Subtract $ 12 $ from $ 64$
$D = \color{#FF6800}{ 52 }$
$\color{#FF6800}{ D } = \color{#FF6800}{ 52 }$
$ $ Since $ D>0 $ , the number of real root of the following quadratic equation is 2 $ $
$ $ 2 real roots $ $
$\alpha + \beta = 8 , \alpha \beta = 3$
Find the sum and product of the two roots of the quadratic equation
$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 8 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 3 } = \color{#FF6800}{ 0 }$
$ $ In the quadratic equation $ ax^{2}+bx+c=0 $ , if the two roots are $ \alpha, \beta $ , then it is $ \alpha + \beta =-\dfrac{b}{a} $ , $ \alpha\times\beta=\dfrac{c}{a}$
$\color{#FF6800}{ \alpha } \color{#FF6800}{ + } \color{#FF6800}{ \beta } = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { - 8 } { 1 } } , \color{#FF6800}{ \alpha } \color{#FF6800}{ \beta } = \color{#FF6800}{ \dfrac { 3 } { 1 } }$
$\alpha + \beta = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { - 8 } { 1 } } , \alpha \beta = \dfrac { 3 } { 1 }$
$ $ Solve the sign of a fraction with a negative sign $ $
$\alpha + \beta = \color{#FF6800}{ \dfrac { 8 } { 1 } } , \alpha \beta = \dfrac { 3 } { 1 }$
$\alpha + \beta = \dfrac { 8 } { \color{#FF6800}{ 1 } } , \alpha \beta = \dfrac { 3 } { 1 }$
$ $ If the denominator is 1, the denominator can be removed $ $
$\alpha + \beta = \color{#FF6800}{ 8 } , \alpha \beta = \dfrac { 3 } { 1 }$
$\alpha + \beta = 8 , \alpha \beta = \dfrac { 3 } { \color{#FF6800}{ 1 } }$
$ $ If the denominator is 1, the denominator can be removed $ $
$\alpha + \beta = 8 , \alpha \beta = \color{#FF6800}{ 3 }$
$ $ 그래프 보기 $ $
Graph
Solution search results
search-thumbnail-
$4x^{2}-8x+3=0$
10th-13th grade
Algebra
Have you found the solution you wanted?
Try again
Try more features at QANDA!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture
apple logogoogle play logo